The Effect of Return on Assets, Current Ratio, and Debt-to-Equity Ratio on Stock Prices: A Case Study of Food and Beverage Sub-Sector Companies Listed on the Indonesia Stock Exchange (2020–2024) - Anita Triana; Tartila Devy (Indonesian Economic Review, 2026)
This study emphasizes the association between corporate financial conditions and share valuation within the food and beverage processing sector listed on Indonesia’s capital market over the past five years by drawing upon documented data derived from audited annual reports, yielding a total of 115 observational records from twenty-three selected firms; the information was examined through data profiling, model feasibility assessment, and relational modeling supported by statistical software. The findings indicate that the capacity of assets to generate earnings does not exhibit a meaningful linkage with stock movements, suggesting that profit magnitude is not invariably a primary consideration for market participants, whereas excessive short-term fund availability demonstrates an inverse tendency, implying perceived inefficiency due to idle resources lacking productive allocation, while the proportional balance between liabilities and equity likewise fails to reveal a pronounced connection with value shifts. Nevertheless, when these elements are evaluated collectively, a substantive relationship with stock price volatility becomes apparent, accounting for more than half of the variation in market value, with the remainder presumably attributable to other determinants beyond the scope of this discussion.